G133 A seemingly isolated inflammatory lesion of the right axilla, with more to the story. (May 2019) - Shepherd, K; Baron, S; Shivamurthy, V; Wilkinson, N
Abstract : This 11-year-old girl presented with an erythematous scaly lesion of her right axilla from the age of 2, which deteriorated over time. Initial skin biopsy at age 4 suggested epidermal naevus with underlying pseudolymphomatous reaction. It was managed with emollients and topical steroids. Extensor erythematous plaques over her knees and elbows were attributed to eczema, and papules over her small joints had been attributed to warts. She had no history of muscle weakness nor functional impairment. A repeat skin biopsy performed at age 10 suggested cutaneous lupus and she was started on hydroxychloroquine along with tacrolimus topically. Five weeks into treatment she developed a rash over her eyelids and was advised to stop the hydroxychloroquine. At the rheumatology review, she had a patch of calcified morphea in the right axilla causing asymmetry of the chest wall and involving the breast. She had a very subtle heliotrope rash and faint Gottron's papules over her knuckles. A photosensitive rash of the face was described. Capillaroscopy identified nailfold capillary abnormalities. Her muscle strength testing was normal. Bloods revealed slight elevation in creatine kinase of 224IU/L and aspartate aminotransferase of 52IU/L, with normal lactate dehydrogenase and inflammatory makers. Myositis antibodies indicated TIF1gamma antibodies, with negative ANA and anti-dsDNA. An MRI confirmed myositis of thigh and buttock muscles, although the muscle biopsy was normal. The patient was treated with intravenous methylprednisolone followed by a weaning course of prednisolone, hydroxychloroquine and methotrexate. Her axillary lesion has significantly improved with less deformity, along with improvements in her Gottron's papules and abnormal capillaroscopy. In the presence of progressive skin lesions involving more than one site, systemic inflammatory conditions should be sought. Skin biopsy findings are often non-specific and over attribution may prevent consideration of a broader differential. Muscle disease can be very subtle or absent in dermatomyositis.